The farmer - Ludy, Mark. (Longmont, Colo. : Green Pastures Pub., 1999)
Although disasters cause a farmer to repeatedly lose his crops, he is rewarded after hopefully continuing to work hard, pray, and help his neighbors.
Keywords: Farm life -- Fiction; Prayer -- Fiction; Miracles -- Fiction; Neighborliness -- Fiction